The protease‐activated receptor 4 Ala120Thr variant alters platelet responsiveness to low‐dose thrombin and protease‐activated receptor 4 desensitization, and is blocked by non‐competitive P2Y12 inhibition. (22nd November 2018) - Whitley, M. J.; Henke, D. M.; Ghazi, A.; Nieman, M.; Stoller, M.; Simon, L. M.; Chen, E.; Vesci, J.; Holinstat, M.; McKenzie, S. E.; Shaw, C. A.; Edelstein, L. C.; et al.
Abstract : Essentials The rs773902 SNP results in differences in platelet protease‐activated receptor (PAR4) function. The functional consequences of rs773902 were analyzed in human platelets and stroke patients. rs773902 affects thrombin‐induced platelet function, PAR4 desensitization, stroke association. Enhanced PAR4 Thr120 effects on platelet function are blocked by ticagrelor. Summary: Background: F2RL3 encodes protease‐activated receptor (PAR) 4 and harbors an A/G single‐nucleotide polymorphism (SNP) (rs773902) with racially dimorphic allelic frequencies. This SNP mediates an alanine to threonine substitution at residue 120 that alters platelet PAR4 activation by the artificial PAR4‐activation peptide (PAR4‐AP) AYPGKF. Objectives: To determine the functional effects of rs773902 on stimulation by a physiological agonist, thrombin, and on antiplatelet antagonist activity. Methods: Healthy human donors were screened and genotyped for rs773902. Platelet function in response to thrombin was assessed without and with antiplatelet antagonists. The association of rs773902 alleles with stroke was assessed in the Stroke Genetics Network study. Results: As compared with rs773902 GG donors, platelets from rs773902 AA donors had increased aggregation in response to subnanomolar concentrations of thrombin, increased granule secretion, and decreased sensitivity to PAR4 desensitization. In the presence of PAR1 blockade, this genotype effect was abolished by higher concentrations of or longer exposure to thrombin. We were unable to detect a genotype effect on thrombin‐induced PAR4 cleavage, dimerization, and lipid raft localization; however, rs773902 AA platelets required a three‐fold higher level of PAR4‐AP for receptor desensitization. Ticagrelor, but not vorapaxar, abolished the PAR4 variant effect on thrombin‐induced platelet aggregation. A significant association of modest effect was detected between the rs773902 A allele and stroke. Conclusion: The F2RL3 rs773902 SNP alters platelet reactivity to thrombin; the allelic effect requires P2Y12, and is not affected by gender. Ticagrelor blocks the enhanced reactivity of rs773902 A platelets. PAR4 encoded by the rs773902 A allele is relatively resistant to desensitization and may contribute to stroke risk.